1. If P(x) =x3+3×2-2x+4, find the value of p(-2) + p(1) + p(0) ?

Question

1. If P(x) =x3+3×2-2x+4, find the value of p(-2) + p(1) + p(0) ?

in progress 0
Genesis 5 months 2022-01-01T18:18:48+00:00 1 Answer 0 views 0

Answers ( )

    0
    2022-01-01T18:20:07+00:00

    Answer:

    22

    Step-by-step explanation:

    p(x) = x³ + 3x² – 2x + 4

    ⇒p(-2) = (-2)³ + 3(-2)² -2(-2) + 4

               = -8 + 3(4) +4 + 4

               = -8 + 12 + 8

               = 12

    ⇒p(1) = (1)³ + 3(1)² -2(1) +4

             = 1 + 3 – 2 +4

             = 6

    ⇒p(0) = (0)³ + 3(0)³ -2(0) + 4

              = 4

    ∴ p(-2) + p(1) + p(0)  = 12 + 6 + 4 = 22

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )